Role of Green Financing in Enhancing Financial Stability of Commercial Banks in Ghana - Mensah, Afia (International Journal of Finance, 2025)
Purpose: The purpose of this article was to analyze role of green financing in enhancing financial stability of commercial banks in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Green financing in Ghana is in its early stages, with limited immediate profitability for commercial banks. However, adopting green finance practices can enhance banks' long-term financial stability by mitigating environmental risks and aligning with global sustainability trends. Initiatives like the Ghana Sustainable Banking Principles, adopted by all 24 commercial banks, aim to integrate environmental and social considerations into banking operations, promoting resilience and stability. Unique Contribution to Theory, Practice and Policy: Stakeholder theory, institutional theory & resource-based view (RBV) may be used to anchor future studies on the role of green financing in enhancing financial stability of commercial banks in Ghana. Commercial banks should develop green finance risk assessment tools to evaluate environmental risks associated with loan and investment portfolios, reducing exposure to high-risk sectors affected by climate change. Central banks and financial regulators should implement green capital adequacy requirements, ensuring that commercial banks allocate a minimum percentage of their loan portfolios to green projects to promote sustainable financial stability.